Penyesuaian dan Kepuasan Perkawinan pada Perempuan Bali yang Tinggal di Keluarga Inti dan Keluarga Batih - Rospita, Indri Oktavia; Lestari, Made Diah (Jurnal Psikologi Udayana; Edisi Khusus, 2016)
Marital satisfaction is not an easy thing to accomplish, especially for wife. Ibrahim (2002) explains that the number of wife which perceive marital satisfaction less than husband. Surya (2001) said that to achieve a successful marriage, the individual must have the ability to adjust. The main adjustment in the overall process of marriage is marital adjustment. Marital adjustment will be more complex for wife who lived with in-law. Balinese women who married and not able to build their own house are required to live in extended family which usually consists of mother-in-law and law. Balinese people also knows other type of  marriage that called nuclear family which the couples lived in separated house of their family. The purpose of this study is to know the correlation between marital adjustment and marital satisfaction on Balinese women who lived in nuclear and extended family and to know the differentiation of marital adjustment and marital satisfaction on Balinese women who lived in nuclear and extended family. This study used quantitative method. Subject were 116 Balinese women who married. The results showed a positive and significant correlation between marital adjustment and marital satisfaction on Balinese women who lived in nuclear family with correlation 0,353 (r>0,05) and probability 0,007 (p<0,05). The similar result also found on Balinese women who lived in extended family with correlation 0,518 (r>0,05) and probability 0,000 (p<0,05). Marital adjustment and marital satisfaction were not different between Balinese women who lived in nuclear or extended family. Keyword : marital adjustment and marital satisfaction, nuclear family, extended family, Balinese women.